Implementasi Strategi Manajemen Talenta dalam Meningkatkan Kinerja Anggota (Studi Kasus di Pusat Informasi dan Konseling Remaja Bangka Jakarta Selatan) - Ramadani, Arya Saputra; Pratama, Ananda Stevvan Vallentino Petrix; Sunarta; Rusliana, Iu (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This research aims to explore the implementation of talent management strategies as a key factor in improving organizational performance, by taking case studies at the Potential Indonesia Jaya Foundation and the Bangka South Jakarta Youth Information and Counseling Center (PIK-R). The approach used in this research is a qualitative approach used to detail the complexity of the interaction between talent management policies and their impact on organizational performance. The research population includes all members involved in talent management strategies at the PIK-R Bangka. The purposive sampling method was used to select respondents who had significant involvement in the talent management program. Data was collected through in-depth interviews, participant observation, and document study. The research results describe the implementation of talent management strategies in the context of non-profit organizations. Data analysis uses a content analysis approach, revealing patterns, themes and relationships between variables that are relevant to improving performance. The results of this research have practical and theoretical implications in the context of human resource management and organizational strategy. Therefore, these findings can be a valuable contribution to the understanding of how the implementation of talent management strategies can be the key to success in improving organizational performance.